Learning Design For Combinatoric With Realistic Mathematics Education Approach - Fitriawan, Dona; Siregar, Nurfadilah (Jurnal Pendidikan MIPA, 2023)
Abstract: The purpose of this research is to design learning combinatorics sub-material factorial, permutation, combination and chance with RME approach. This research is a qualitative research. With this research method using design research. The research techniques used are measurement techniques, direct observation and documentation with tools in the form of objective tests, observation sheets and document sheets. The research subjects were 2 classes, namely A1 and A2 classes in the Mathematics Education Mathematics Statistics course specifically combinatorics material totaling 35 students with the learning trajectory in the form of numbers that were applied alternately to students. The conclusion of this research is obtained: 1) in the factorial sub-material, students are introduced to the RME approach that 4!= 24 , 3!= 6, 2!= 2 , 1!=1until it is proven that 1!=1in the permutation and combination sub material, students are directed to be examples of the same numbers and letters that form the rules of permutation and combination in the opportunity sub-material, students are exemplified about coins and dice, both in one, two, and three pieces in the context of the problem. Keywords: learning design, rme approach, design research Abstrak: Tujuan dari penelitian ini adalah mendesain pembelajaran materi kombinatorika sub materi factorial, permutasi, kombinasi dan peluang dengan pendekatan RME. Penelitian ini berjenis penelitian kualitatif. Dengan metode penelitian ini menggunakan design research. Teknik penelitian yang digunakan adalah teknik pengukuran, observasi langsung dan dokumentasi dengan alatnya berupa tes objektif, lembar pengamatan dan lembar dokumen. Subjek penelitiannya ada 2 kelas yaitu kelas A1 dan A2 pada mata kuliah Statistika Matematika Pendidikan Matematika terkhusus materi kombinatorika berjumlah 35 mahasiswa dengan lintasan belajarnya berupa Number-Number yang diterapkan secara bergantian ke mahasiswa. Kesimpulan dari penelitian ini diperoleh: 1) pada sub materi factorial, peserta didik dikenalkan dengan pendekatan RME bahwa 4!= 24 , 3!= 6, 2!= 2 , 1!=1 sampai dibuktikan bahwa 1!=1 pada sub materi permutasi dan kombinasi, peserta didik diarahkan for menjadi contoh Number dan huruf yang sama sehingga membentuk aturan permutasi dan kombinasi tersebut pada sub materi peluang, peserta didik dicontohkan tentang mata uang logam dan dadu, baik dalam sebuah, dua buah, maupun tiga buah dalam konteks masalah. Kata kunci: desain pembelajaran, pendekatan rme, penelitian desainDOI: http://dx.doi.org/10.23960/jpmipa/v24i3.pp594-602